Changes in geomagnetic activity and global temperature during the past 40 years - Bucha, V. (Václav) (Studia Geophysica et Geodaetica, 2012)
The purpose of this study is to investigate the effect of geomagnetic activity (used as a measure of solar wind parameters) on the variability of large-scale climate patterns and on changes in the global temperature. We show that positive statistically significant correlations between global temperature and the distribution of surface temperature over Eurasia, the East and Equatorial Pacific and over the North Atlantic for the period 19662009 correspond to large-scale climate patterns defined by climate indices. We found very similar positive correlations between geomagnetic activity and the distribution of surface temperature in the mentioned regions. As an effect of geomagnetic storms, energetic particles penetrate from the magnetosphere into the region of the stratospheric polar vortex. The increase of temperature and pressure can be observed over northern Canada. The vortex shifts towards Europe, rotates counter-clockwise and the wind blows from the polar region over the Norwegian Sea southwards.